Zoonotic viruses in northern Eurasia : taxonomy and ecology /: taxonomy and ecology. (2015) - Lʹvov, Dmitriĭ Konstantinovich; Shchelkanov, Mikhail; Alkhovsky, Sergey; Deryabin, Petr Grigorievich
No abstract available